Overexpression of Bacillus circulans alkaline protease in Bacillus subtilis and its potential application for recovery of protein from soybean dregs - Chen, Hao; Wu, Jie; Huang, Xiaodan; Feng, Xuzhong; Ji, Hongwu; Zhao, Liangzhong; Wang, Jianrong (Frontiers in Microbiology, 2022)
Proteases are important for decomposition of proteins to generate peptides or amino acids and have a broad range of applications in different industries. Herein, a gene encoding an alkaline protease (AprBcp) from Bacillus circulans R1 was cloned and bioinformatics analyzed. In addition, a series of strategies were applied to achieve high level expression of AprBcp in Bacillus subtilis. The maximum activity of AprBcp reached 165870 U/mL after 60 h fed-batch cultivation in 50 L bioreactor. The purified recombinant AprBcp exhibited maximum activity at 60 ℃ and pH 10.0, and remained stable in range from pH 8.0 to 11.0 and 30 to 45 ℃. Metal ions Ca2+, Mn2+ and Mg2+ could improve the stability of AprBcp. Furthermore, the recombinant AprBcp displayed great potential application on recovery of protein from soybean dregs. The results of this study will provide an effective method to prepare AprBcp in B. subtilis and its potential application on utilization of soybean dregs.